Explaining the “female victim effect” in capital punishment: an examination of victim sex–specific models of juror sentence decision-making - Richards, Tara N. (Crime & delinquency, 2016)
Only a limited body of research has focused on how victim sex may affect capital sentencing decisions. Acknowledging this issue, the present study uses a large sample of capital cases from North Carolina (n = 709) and victim sex–specific logistic regression models to examine whether different variables are important predictors of receiving the death penalty for male victim cases versus female victim cases. Results indicate that (a) sex-specific models better explain juror death penalty decision-making compared with a full model, including victims of both sexes, and (b) different extralegal and legal characteristics predict jurors’ decisions to choose the death penalty in cases with male victims versus female victims. Specifically, for male victims, older victim age, younger defendant age, urban jurisdiction, the number of victims killed, the number of aggravators, the number of mitigators, and case designation as heinous and cruel predict juror decision-making. Comparatively, for female victim cases, only the number of mitigators and case designation as heinous and cruel are significant predictors. Theoretical and legal implications as well as directions for future research are discussed.